Developing Bots with Microsoft Bots Framework Create Intelligent Bots using MS Bot Framework and Azure Cognitive Services - Machiraju, Srikanth (Apress, 2018)
Develop Intelligent Bots using Microsoft Bot framework (C# and Node.js), Visual Studio Enterprise & Code, Microsoft Azure and Cognitive Services. This book shows you how to develop great Bots, publish to Azure and register with Bot portal so that customers can connect and communicate using famous communication channels like Skype, Slack, Web and Facebook. You'll also learn how to build intelligence into Bots using Azure Cognitive Services like LUIS, OCR, Speech to Text and Web Search. Bots are the new face of user experience. Conversational User Interface provides many options to make user experience richer, innovative and engaging with email, text, buttons or voice as the medium for communication. Modern line of business applications can be replaced or associated with intelligent Bots that can use data/history combined with Machine intelligence to make user experience inclusive and exciting. With Developing Bots with Microsoft Bots Framework, you'll see just how simple Bot building can be.